Motivation Factors On Knowledge Sharing Among Public Sector Organizations In Malaysia - Azhar, Nurin Hanani Baharul (2012)
A study has been conducted to explore the motivation factors on knowledge sharing among public sector organizations in Malaysia. Nowadays, knowledge management (KM) has been identified by most of the organizations as a positive force in creating new knowledge hence increase sustainable competitive advantage. Many researchers have agreed on the importance of knowledge management as the process that should integrate individual talents, culture and technology to increase the knowledge generated throughout the organizations. Knowledge sharing is the most essential part in the implementation of knowledge management. Application of knowledge sharing culture in both public and private sector organizations may develop efficiency and effectiveness of service delivery. Malaysia's public sectors have promoted numbers of key measures to enhance economy wide productivity, accelerate economic growth as well as to develop innovation and creativity towards better quality, responsive and knowledge-based public services.